2021
DOI: 10.1155/2021/7340140
|View full text |Cite|
|
Sign up to set email alerts
|

Design of the Exercise Load Data Monitoring System for Exercise Training Based on the Neural Network

Abstract: In order to monitor the sports load data of athletes in sports training, this paper studies the methods and systems of sports load monitoring and fatigue warning based on neural network technology. In this paper, the neural network parallel optimization algorithm based on big data is used to accurately estimate the motion load and intensity according to the determined motion mode and acceleration data, so as to realize the real-time monitoring of the exercise training. The results show that the value of η is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…An diesem Punkt kann der Einsatz von KI eine Verbesserung der aktuellen Versorgung bedeuten. Eine genaue Klassifizierung der sportlichen Leistung und der daraus resultierenden Erschöpfung und Verletzungsanfälligkeit kann durch den Einsatz KI vorausgesagt und besser gesteuert werden 14 15 16 17 . Die verbesserte Evaluierung der Trainingsleistung wurde jedoch nur bei professionellen Athleten dargestellt.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…An diesem Punkt kann der Einsatz von KI eine Verbesserung der aktuellen Versorgung bedeuten. Eine genaue Klassifizierung der sportlichen Leistung und der daraus resultierenden Erschöpfung und Verletzungsanfälligkeit kann durch den Einsatz KI vorausgesagt und besser gesteuert werden 14 15 16 17 . Die verbesserte Evaluierung der Trainingsleistung wurde jedoch nur bei professionellen Athleten dargestellt.…”
Section: Introductionunclassified
“…Jedoch gilt es, insbesondere bei Palliativpatienten, eine Überlastung zu vermeiden. Der Einsatz von KI kann hierbei hilfreich sein 14 . Das Ziel dieser Pilotstudie war daher die Analyse der Machbarkeit einer Unterstützung der Trainingssteuerung durch KI bei Palliativpatienten.…”
Section: Introductionunclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%